Preparation and characterization of polycaprolactone-collagen loaded gentamicin sulphate nanofibers by electrospinning - Abdul Hakim bin Abdul Razak (Kulliyyah of Science, International Islamic University Malaysia, 2018)
Combination of synthetic and natural polymers have broadened the scope for development of nanofibrous scaffolds. This combination was believed could promote greater properties of nanofibers to be used in the field of tissue engineering. Indeed, the latest advancement in the nanofiber production was to incorporate therapeutically agent in order to improve its functions as a drug carrier to target area. The effective scaffolds should have properties and delivery characteristics that are suitable for specific wound types with convenience property to the patient and at rational cost. Thus some modification of the physical characteristics of the wound dressing systems is essential. In this study, nanofibers from polycaprolactone (PCL)/collagen loaded with gentamicin sulphate were prepared using electrospinning technique. Scanning electron microscopy (SEM) micrograph of PCL/Collagen (3:1) nanofibers showed smooth and fine fibers with average fibers diameter 121.37 ± 18.02 nm and for PCL/collagen (3:1) loaded 1% gentamicin sulphate showed smooth, finer and less beads formation with average fiber diameters 123.66 ± 34.20 nm. The increment of gentamicin sulphate concentration leads to the increase fiber diameter. Moreover, the drug release revealed sustained release patterns for nanofibers loaded 1%, 3% and 5% gentamicin with the highest release percentage of 5% gentamicin concentration. The MTT assay demonstrated high viability of normal human fibroblast cells on PCL/collagen nanofibers with and without gentamicin sulphate after 5 days. The antibacterial study for PCL/Collagen loaded gentamicin sulphate nanofiber shown high inhibition for both bacterial strain, gram negative escherichia coli and gram positive staphylococcus aureus for all PCL/collagen loaded gentamicin sulphate nanofibers for 3 days of incubation. Therefore, PCL/collagen loaded gentamicin sulphate nanofiber can be potential for skin tissue engineering